Increased biologically effective dose (BED) to the primary tumor is associated with improved survival in patients with oligometastatic NSCLC. (October 2021) - Farooqi, Ahsan; Ludmir, Ethan B.; Mitchell, Kyle G.; Antonoff, Mara B.; Tang, Chad; Lee, Percy; Chang, Joe; Elamin, Yasir; Gomez, Daniel R.; Gandhi, Saumil J.
Highlights: Radiation to the primary tumor can improve survival in metastatic lung cancer. Unclear if higher effective dose of radiation help in this setting. We found higher effective radiation doses improve local control of tumor. Our data also suggests higher effective radiation doses improve survival. Abstract: Purpose: Local consolidative therapy (LCT) for oligometastatic non-small cell lung cancer (NSCLC) is an evolving treatment paradigm. We investigated whether the biologically effective dose (BED) of consolidative radiation therapy (RT) to the primary tumor predicted for improved local control, progression-free survival (PFS), and overall survival (OS) among NSCLC patients presenting with oligometastatic disease. Materials and methods: Patients presenting to a single institution (2000–2017) with stage IV NSCLC, ≤3 synchronous metastatic lesions at diagnosis, and treated with RT to the primary tumor were identified. Univariate and multivariable Cox proportional-hazards regression modeling were performed to identify factors associated with local recurrence-free survival (LRFS), PFS, and OS. Results: One hundred twenty-four patients were identified meeting our inclusion criteria. With a median follow-up of 55.1 months, median PFS and OS for the entire cohort were 11.0 months and 25.3 months, respectively. The median BED (α/β = 10) of RT to the primary tumor was 74.3 Gy. On univariate analysis, increased BED to the primary tumor predicted for improved PFS ( p  < 0.001) and LRFS ( p  = 0.01), with a median PFS of 8.5 vs 12.8 months and median LRFS of 23.4 vs 58.4 months between patients treated with BED < 75 Gy and ≥75 Gy, respectively. Increased BED to the primary tumor was also associated with significantly improved OS ( p  = 0.02); patients treated with a BED of <75 Gy demonstrated a median OS of 22.9 months vs 27.5 months if treated with BED ≥ 75 Gy. On multivariable analysis, primary site BED remained a significant predictor of OS ( p  = 0.02) and PFS ( p  = 0.002). Conclusions: We found that delivery of >75 Gy BED RT regimens to the primary lesion in patients with synchronous oligometastatic NSCLC is associated with improved local control, PFS, and OS. These data support results of recent prospective trials and other ongoing prospective efforts to characterize therapeutic benefits associated with this management strategy.